2008
DOI: 10.1007/s10562-008-9650-y
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy Study of γ-Al2O3 Supported Cobalt Fischer–Tropsch Synthesis Catalysts

Abstract: Three supported catalysts containing 20 wt% cobalt and 0.5 wt% rhenium were subjected to electron microscopy studies in their calcined state. The catalysts were prepared by incipient wetness impregnation of c-Al 2 O 3 supports of different pore characteristics with aqueous solutions of cobalt nitrate hexahydrate and perrhenic acid. The influence of the support on the Co 3 O 4 crystallite size and distribution was studied by X-ray diffraction and electron microscopy. There was a positive correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 24 publications
6
33
0
Order By: Relevance
“…The formation of nanoparticle aggregates has previously been shown for Co/Al 2 O 3 and Co/SiO 2 FTS catalysts. 38,40,41 We demonstrate here that aggregates of Co nanoparticles are also formed using TiO 2 as support. The formation of aggregates of nanoparticles is most probably related to the drying temperature of the catalyst.…”
Section: Resultsmentioning
confidence: 59%
“…The formation of nanoparticle aggregates has previously been shown for Co/Al 2 O 3 and Co/SiO 2 FTS catalysts. 38,40,41 We demonstrate here that aggregates of Co nanoparticles are also formed using TiO 2 as support. The formation of aggregates of nanoparticles is most probably related to the drying temperature of the catalyst.…”
Section: Resultsmentioning
confidence: 59%
“…The nanoparticles interact more readily with the support [21] making them more difficult to reduce. Preliminary reduction experiments performed on c-Al 2 O 3 catalysts in the ETEM, confirmed that they were more difficult to reduce and that the degree of reduction was not so easy to establish due to the more complicated microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with earlier interpretation by Iglesia et al 1 and with experimental results obtained with rhenium and platinum as reduction promoters. 16,18,19 A recent report has rather concluded on the existence of bimetallic Co-containing Ru nanoparticles, on the basis of XAS recorded at the Ru K edge. 84 In that case, catalysts were prepared by sequential impregnation on a formerly calcined Co catalyst, which may explain the differences in terms of interactions between Co and Ru.…”
Section: Acs Catalysismentioning
confidence: 99%